Hypnobirthing And Rebozo Affect The Duration Of Labor In II And Apgar Scores - Desy Syswianti; Tri Wahyuni (JKM (Jurnal Kebidanan Malahayati), 2023)
Latar Belakang: Angka kematinan ibu dan angka kematian bayi di Indonesia masih tinggi. Partus lama menjadi penyebab 31% kematian ibu. Adapun kematian bayi 27,4% disebabkan karena asfiksia. Asfiksia dapat dideteksi dengan melalui pengukuran skor Apgar. Pemberian hypnobirthing dan teknik rebozo dipercaya dapat mempercepat lama persalinan kala II dan meningkatkan skor Apgar.Tujuan: Mengetahui pengaruh pemberian hypnobirthing dan rebozo terhadap lama persalinan kala II dan skor Apgar.Metode: Penelitian merupakan quasy experiment, dengan desain posttest only with control group design, di mana kelompok eksperimen diberikan hypnobirthing dan rebozo dan kelompok kontrol hanya diberikan hypnobirthing. Populasi adalah ibu melahirkan di BPM Bidan D di Garut pada periode November – Desember 2021. Sampel masing-masing kelompok sejumlah 20 ibu melahirkan, diambil dengan purposive sampling. Pengukuran lama persalinan kala II digunakan stopwatch dan pada skor Apgar digunakan tes Apgar. Analisis data digunakan uji t sampel independen  apabila data penelitian distribusi data normal, dan uji Mann Whitney apabila data penelitian tidak distribusi data normal.Hasil: Hasil pengujian Mann-Whitney menunjukkan bahwa pemberian hypnobirthing dan rebozo berpengaruh terhadap lama persalinan kala II, ditunjukkan dari nilai Z sebesar -4,420 dan p sebesar 0,000 (p<0,05). pemberian hypnobirthing dan rebozo tidak berpengaruh terhadap skor Apgar, ditunjukkan dari nilai Z sebesar --0,284 dan p sebesar 0,776 (p>0,05).Kesimpulan:  Pemberian hypnobirthing dan rebozo berpengaruh terhadap penurunan lama persalinan kala II, dan tidak berpengaruh terhadap skor Apgar.Saran:  hendaknya bidan membuat suatu video pembelajaran teknik hypnobirthing dan rebozo, agar ibu hamil dapat menerapkan teknik hypnobirthing selama masa kehamilan, dan sebagai pembelajaran bagi bidan agar dapat membantu ibu bersalin dalam melakukan teknik rebozo. Kata kunci: Skor Apgar, Hypnobirthing, Lama Persalinan Kala II ABSTRACT Background: Maternal and infant mortality rates in Indonesia are still high. Long parturition is the cause of 31% of maternal deaths. The 27.4% infant mortality was caused by asphyxia. Asphyxia can be detected by measuring the Apgar score. Giving hypnobirthing and rebozo technique is believed to speed up the duration of the second stage of labor and increase the Apgar score.Purpose: To determine the effect of hypnobirthing and rebozo on the duration of the second stage of labor and the Apgar score.Methods:  This research is a quasi experiment, with a posttest only design with control group design, where the experimental group was given hypnobirthing and rebozo and the control group was only given hypnobirthing. The population is mothers giving birth at BPM Midwife Dina Garut in the period November – December 2021. The sample of each group is 20 mothers who give birth, taken by purposive sampling. The measurement of the duration of the second stage of labor was used a stopwatch and the Apgar score was used for the Apgar test. Data analysis used the independent sample t test if the research data was normally distributed, and the Mann Whitney test if the research data was not normally distributed.Result: The results of the Mann-Whitney test showed that hypnobirthing and rebozo had an effect on the duration of the second stage of labor, indicated by the Z value of -4.420 and p of 0.000 (p<0.05). giving hypnobirthing and rebozo had no effect on Apgar score, indicated by Z value of -0.284 and p of 0.776 (p>0.05).Conclusion: The implementation of hypnobirthing and rebozo had an effect on decreasing the length of the second stage of labor, and had no effect on the Apgar score.Suggestion: Midwives should make a video learning the hypnobirthing and rebozo techniques, so that pregnant women can apply the hypnobirthing technique during pregnancy, and as a lesson for midwives so they can help mothers in childbirth in doing the rebozo technique. Keywords: Apgar Score, Hypnobirthing, Second Stage Labor Duration